3D seismic insights into lithological controls on igneous intrusion-induced ground deformation - Magee,C; Briggs,F; Jackson,CAL (Journal of the Geological Society, 2013)
Ground deformation commonly precedes volcanic eruptions, although its relationship to underlying intrusion networks is complex. We use 3D seismic reflection data to examine the link between a saucer-shaped sill and an overlying forced fold formed at the contemporaneous palaeosurface. Our results highlight a disparity in size between the sill and fold, which we attribute to accommodation of magma by overburden uplift and fluid expulsion from the host rock. Sill transgression occurred in response to plastic deformation of the host rock and did not produce seismically resolvable uplift. Inversion models of ground deformation should therefore acknowledge host rock behaviour during intrusion.